Similative morphemes as purpose clause markers in Ethiopia and beyond - (:unkn) unknown (My University, 2017)
In more than 30 languages spoken at the Horn of Africa, a similative morpheme 'like' or a noun 'manner' or 'type' is used as a marker of purpose clauses. The paper first elaborates on the many functions of the enclitic morpheme =g 'manner' in Kambaata (Highland East Cushitic), which is used, among others, as a marker of the standard in similative and equative comparison ('like', 'as'), of temporal clauses of immediate anteriority ('as soon as'), of complement clauses ('that') and, most notably, of purpose clauses ('in order to'). The second part of the paper gives a detailed account of the distribution of the use of 'like', 'manner' or 'type' as a purpose clause marker in Afroasiatic and Nilo-Saharan languages of the Horn of Africa. Similative-purpose multifunctionality, which is cross-linguistically rare, concentrates especially in central areas of Ethiopia and can be assumed to be the result of language contact between certain Cushitic, Ethio-Semitic and Omotic languages.
Keywords: African Research